2015
DOI: 10.1111/nph.13681
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Nicotiana attenuata LHY and ZTL alters circadian rhythms in flowers

Abstract: SummaryThe rhythmic opening/closing and volatile emissions of flowers are known to attract pollinators at specific times. That these rhythms are maintained under constant light or dark conditions suggests a circadian clock involvement. Although a forward and reverse genetic approach has led to the identification of core circadian clock components in Arabidopsis thaliana, the involvement of these clock components in floral rhythms has remained untested, probably because of the weak diurnal rhythms in A. thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 60 publications
(115 reference statements)
2
61
1
1
Order By: Relevance
“…However, though our results have some degree of similarities with elf3 mutants, the circadian clock is a complex system and variations can be found from species to species, so the reason for the variable period length in LL in P. umbraticola will remains unclear until there is further molecular evidence. Recent studies in Nicotiana attenuata have reported that silencing of clock component genes NaLHY and NaZTL resulted in altered circadian rhythms of flower opening, floral scent emission, and vertical movement of flowers (Yon et al, 2016). This report clearly demonstrated the involvement of the circadian clock components in the rhythmic regulation of physiological processes in floral organs.…”
Section: Discussionsupporting
confidence: 55%
“…However, though our results have some degree of similarities with elf3 mutants, the circadian clock is a complex system and variations can be found from species to species, so the reason for the variable period length in LL in P. umbraticola will remains unclear until there is further molecular evidence. Recent studies in Nicotiana attenuata have reported that silencing of clock component genes NaLHY and NaZTL resulted in altered circadian rhythms of flower opening, floral scent emission, and vertical movement of flowers (Yon et al, 2016). This report clearly demonstrated the involvement of the circadian clock components in the rhythmic regulation of physiological processes in floral organs.…”
Section: Discussionsupporting
confidence: 55%
“…Plant growth conditions and phenotyping T 3 homozygous irLHY-406, and irZTL-314 (Yon et al 2016) were used for all pollination experiments described in this study, and the 31 st inbred generation wild-type (WT) Nicotiana attenuata plants were used as pollen donors. In the field, seedlings were transferred into hydrated 50 mm peat pellets and later transplanted to an irrigated field plot at the Lytle Ranch Preserve, as described in Kessler et al 2012.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the floral scents of Petunia are under the control of internal clocks, called the circadian clock, and synchronize emissions with the active time of the flower's pollinators (Hoballah et al 2005;Fenske et al 2015). Flower opening/closing and flower movement are also regulated by the circadian clock (Atamian et al 2016;Yon et al 2016). However, it remains largely untested how the circadian clock functions for a plant's reproductive success in nature when more than one pollinator species are available.…”
mentioning
confidence: 99%
See 2 more Smart Citations